SOLUSI MODEL LINEAR NAVIER-STOKES-KORTEWEG DI R_+^3 DENGAN SYARAT BATAS SLIP - Jihandika Prayugo; Suma Inna; Mahmudi Mahmudi; Nia Damiati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This article discusses the solution of the linear Navier-Stokes-Korteweg model in  considering slip boundary conditions. This model is often used to describe the two-phase flow of fluids, where there is a phase change at the interface known as the capillary effect. To overcome the impact of the capillary effect, Korteweg developed the Navier-Stokes model by incorporating the element of capillary into the Navier-Stokes equations. The results of this article show that the Korteweg-type Navier-Stokes model has a solution for the coefficient case  with . The emergence of this coefficient case is related to the condition of the roots of the characteristic equation of the model described in this article.